SISTEM INFORMASI PEMESANAN MENU MAKANAN PADA RESTORAN EIGHTEEN PIES BERBASIS WEB - Muhamad Dendi; Nurjaya (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
This research was conducted to be able to create a dining menu ordering system at the Eighteen Pies restaurant that can provide all information about food lists and drink lists to food stocks, to financial reports at the cashier. The methodology used in the design of this information system uses Waterfall, this methodology can be used as a methodology to analyze and design a Dining Menu Ordering Information System at the Eighteen Pies Restaurant. The results of the study indicate that the use of a web-based meal ordering information system as an improvement or improvement of existing facilities and infrastructure so as to improve employee performance in serving customers can indirectly increase income at the Eighteen Pies restaurant.,